Rethinking Rhetoric: An investigation of political persuasion online. A case study of Mauritian electoral interviews livestreamed on Facebook - Suddason, Kelvin (Centre for Film and Media Studies, 2021)
The live-commenting feature Facebook Live offers a unique look into how persuasion operates online. By giving citizen-users, or the viewertariat (see Anstead & O'Loughlin, 2011), the opportunity to comment on live political performances, Facebook Live presents a worthy site of investigation into how traditionally-powerful performer-persuaders (electoral candidates) now face off with traditionally-excluded masses of audience-persuadees (citizen-users). The livestream then becomes a mediated space of contestation, where the boundaries between persuader-persuadee and performer-audience fades, where, this study proposes, persuadee becomes persuader, rendering, in the process, the traditional persuader less persuasive, and thus less powerful. The study sought to understand how electoral persuasion operates online in Mauritius by using the Facebook livestreamed interviews of three candidates (incumbent, long-time, and first-time candidate) running in the December 2017 By-Election. A combined rhetorical and content analysis was conducted on candidates' representative claims (see Saward, 2006) and the viewertariat responses to these claims. This study finds that candidates employ a self-centred rhetoric, focusing on their ‘candidateness' rather than their representativeness, which, this study proposes, has ramifications on how candidates approach politics in contemporary Mauritius. The study also finds that the viewertariat is actively engaged in counter-persuasion, constructing their own (re)representative claims and exchanging primarily with other viewertariat members and lurkers (see Hill & Hughes, 1997). The viewertariat exhibits horizontal persuasion which, this study discusses, dilutes the vertical persuasion employed by candidates. The overall findings lead to the conclusion that rhetoric as a theoretical framework must be extended to adequately capture the persuasive dynamics in online electoral public spheres. A new theoretical framework is finally proposed, with the tripartite distinction between performer-text-audience rearranged to include performer-persuasive text-viewertariat-lurkers, and complemented with an argument as to the growing conceptual obsolescence of the ‘audience' in studying rhetoric online.